Effect of potassium-competitive acid blockers on human gut microbiota: a systematic review and meta-analysis - Ouyang, Meng-Ling; Zou, Shu-Peng; Cheng, Qian; Shi, Xuan; Zhao, Ya-Zheng; Sun, Ming-Hui (Frontiers in Pharmacology, 2023)
Background: Vonoprazan has been reported to exert more potent and long-lasting gastric acid inhibition than proton pump inhibitors, potentially leading to a greater impact on the gut microbiota.This study aimed to clarify changes in microbial diversity and bacterial composition after VPZ treatments.We searched from PubMed, Embase, WOS, Scopus, Cochrane Library, and ClinicalTrials.gov (all years up to May 2023). The primary outcomes were alpha and beta diversity, as well as differences in gut microbiota composition between before and after VPZ treatments. We performed a meta-analysis to uncover the potential changes in human gut microbiota among VPZ users by pooled mean difference (MD) with a 95% confidence interval (CI). The risk of bias was assessed using the ROBINS-I tool.Results: A total of 10 studies were included to compare differences before and after VPZ treatments.Compared with baseline, alpha diversity was significantly reduced after VPZ treatments and gradually returned to baseline with longer follow-up. At the phylum level, there was a decrease in the relative abundance of Firmicutes and Actinobacteria, while Bacteroidetes increased compared with baseline.At the genus level, we found a significant decrease in the relative abundance of Coprococcus and Bifidobacterium and a significant increase in the relative abundance of Bacteroides compared with those before treatment. In subgroup analyses according to country and participants, we found differences in microbial changes after VPZ treatments.Vonoprazan can affect the changes of gut microbiota, which may be potentially associated with its strong ability of acid inhibition. However, due to the large heterogeneity, further studies are required to validate these findings.